2021
DOI: 10.1177/10664807211009809
|View full text |Cite
|
Sign up to set email alerts
|

Marital Satisfaction of Portuguese Families in Times of Social Lockdown

Abstract: The COVID-19 pandemic represents a global threat and crisis situation, and its wide-reaching impact has also affected marital satisfaction. Dysfunction of the marital system puts the survival of the family unit at risk. This research aimed to determine the level of marital satisfaction of Portuguese families during the social lockdown and the association between the variables under study. A descriptive, exploratory study was conducted. During the social lockdown, 276 people of Portuguese nationality and residi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The Covid-19 pandemic not only caused a health crisis, but it also disrupted many aspects of human life. Previous research found that the Covid-19 pandemic had a negative impact on Indonesia's labor market, economic, and mental health ( Fernandes et al, 2021 ). During the early stages of pandemic, negative emotions such as anxiety, sadness, anger, and fear were observed in Indonesian families living in West Java ( Ramadhana, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Covid-19 pandemic not only caused a health crisis, but it also disrupted many aspects of human life. Previous research found that the Covid-19 pandemic had a negative impact on Indonesia's labor market, economic, and mental health ( Fernandes et al, 2021 ). During the early stages of pandemic, negative emotions such as anxiety, sadness, anger, and fear were observed in Indonesian families living in West Java ( Ramadhana, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pandemic hardships posed a risk to family resilience ( Eales et al, 2021 ; Gayatri & Irawaty, 2021 ; Prime et al, 2020 ). Several previous studies have found the associations between the hardships of the Covid-19 pandemic and the couples’ relationship ( Fernandes et al, 2021 ; Pietromonaco & Overall, 2021 ; Schmid et al, 2021 ). Some studies found that divorce rates increased during the pandemic compared to before the pandemic ( Goodwin et al, 2020 ; Zhu et al, 2021 ), while others found that they decreased ( Fallesen, 2021 ; Kim & Kim, 2021 ; Manning & Payne, 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…Um estudo realizado com 781 indivíduos alemães em coabitação indicou que a satisfação conjugal diminuiu para 40% da amostra após o início da pandemia, permaneceu estável para outros 40% e aumentou para os demais (Schmid, Wörn, Hank, Sawatzki, & Walper, 2021). Em uma amostra de 276 portugueses, verificou-se níveis médios de satisfação conjugal durante os primeiros meses de pandemia (Fernandes, Magalhães, Silva, & Edra, 2021). De modo geral, os estudos que investigam a satisfação conjugal a compreendem como uma avaliação global e subjetiva que cada cônjuge faz do relacionamento (Delatorre & Wagner, 2022).…”
Section: Introductionunclassified
“… 15 Marital satisfaction and quality of sexual life are two components of sexual life that may be affected by the individual, family and social effects during critical situations such as the COVID-19 pandemic. 16 17 …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the negative impact of the COVID-19 pandemic on individuals’ sexual lives has been reported in countries such as Spain, Italy and Iran 15. Marital satisfaction and quality of sexual life are two components of sexual life that may be affected by the individual, family and social effects during critical situations such as the COVID-19 pandemic 16 17…”
Section: Introductionmentioning
confidence: 99%